DNA-damage response as a novel pathogenic mechanism of heart failure with preserved ejection fraction. (10th June 2022) - Stadiotti, I; Santoro, R; Scopece, A; Pirola, S; Guarino, A; Ascione, F; Li, Q; Delia, D; Foiani, M; Pompilio, G; Sommariva, E
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Italian Ministry of Health Background: Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous syndrome characterized by impaired left ventricular (LV) diastolic function, with normal LV ejection fraction. The most common cause is aortic valve stenosis, which provokes sustained pressure overload (PO) (1). HFpEF cardiac remodeling comprises cardiomyocyte (CM) hypertrophy and fibrotic matrix deposition (2). A link between HFpEF pathogenesis and DNA damage response (DDR) activation emerged from in vivo studies (3). DNA damage activates DDR kinases, producing the phosphorylation of H2AX histone and checkpoint proteins, CHK1 and CHK2, to orchestrate cell recovery. DDR activation contributes to mouse CM hypertrophy and inflammation, promoting cardiac remodeling and HF (4)(5). No studies of this molecular mechanism have been performed on HFpEF patient samples yet. Moreover, known the pivotal role of the stromal compartment in the myocardial response to PO (6)(7), the effects of DDR activation on cardiac mesenchymal stromal cells (C-MSC) are still to be investigated. Purpose: Our aim is to address the aforementioned gaps, unraveling the effects of C-MSC DDR persistent activation on C-MSC phenotypes. Methods: We collected LV septum samples from patients with HFpEF undergoing aortic valve surgery (n=7) and healthy controls (HC; n=7), both for tissue analyses and C-MSC isolation. PO-induced mechanical stimuli has been simulated in vitro by cyclic unidirectional stretch. Results: Histological analyses of HFpEF tissues showed enlarged nuclei and hypertrophic cardiac fibers, increased collagen deposition, higher apoptosis and oxidative stress than HC tissues. HFpEF samples revealed DNA damage (% γH2AX positive cells p=0.047), in both CM and C-MSC. γH2AX, pCHK1, pCHK2 protein expression was higher in HFpEF total tissue (γH2AX/GAPDH p= 0.033; pCHK1/GAPDH p= 0.018; pCHK2/GAPDH p= 0.049). Primary human C-MSC isolated from HFpEF and HC cardiac tissues confirmed the increased γH2AX (γH2AX/GAPDH p=0.0030) and phosphorylated checkpoint protein expression (pCHK1/GAPDH p= 0.045; pCHK2/GAPDH p= 0.039), suggesting C-MSC involvement in DDR-driven remodeling. HFpEF C-MSC express also more pro-fibrotic and pro-inflammatory factors than HC cells. In response to in vitro mechanical stimulation, HC C-MSC increased DNA damage (% γH2AX positive cells non-stretched vs. stretched cells p=0.022) and phosphorylated checkpoint proteins, suggesting PO-guided activation of DDR. Stretched C-MSC secreted more pro-inflammatory and pro-fibrotic molecules compared to static control. Conclusion: HFpEF sustained PO induces DDR persistent activation not only in CM but also in C-MSC. On C-MSC, DDR impairments are linked to inflammation and fibrosis, with direct effects on C-MSC protein expression and secretome. The factors released by C-MSC could further impair CM function. Future studies will unravel the potential anti-fibrotic and anti-hypertrophic effects of DDR inhibitors in HFpEF context.